Information system and productivity in Kuwaiti public organizations: looking inside the black box - Almutairi, Helaiel (2007)
This study investigated the impact of information system on productivity in Kuwaiti public organizations. More specifically, it investigated the impact on business processes. Three dimensions of these processes were selected to view the impact. These dimensions were: Internal Process Performance, Coordination, and Customer Focus. Based on the literature review, three hypotheses were formulated. Each hypothesis related Information System usage to an increase in the efficiency of the three process dimensions. In addition, this study investigated the impact of ten more variables that might affect the dependent variables. these variables included age, gender, nationality, years of experience in Kuwaiti public sector, years of experience in the current organization, years of experience in using IS, years of training in IS, position in hierarchy, level of education and years spent in current position. The study found a significant statistical evidence for the relationship between the usage of information system in a process and increasing the efficiency of its Internal Performance, Coordination, in a process and increasing the efficiency of its Internal Performance, Coordination, and Customer Focus. Further, five of the ten additional variables were found to be significant. Research and practice implications of the study's findings were stated. - Reproduced.
Keywords: Information system - Kuwait; Information system